CONCEPT OF IDEOLOGY: VIEWS OF MAJOR POLITICAL THINKERS - R., Girija (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper describes the meaning, functions and characteristics of ideology. According to Antoine Louis Claude Destutt de Tracy, ideology was a study of the process of forming ideas and a science of ideas. Two aspects of his theories should be noted. The first is materialism thought and the second is Social and political improvement. Ideology performs many functions that is solidarity and mobilization, organization, expression, manipulation, communication and affect. Ideology arises in conditions of crisis and in sections of society. It has a broad but varying scope and is a systematic pattern of political thought. Political ideologies are divided into statuesque ideologies, revolutionary ideologies and reformist ideologies. Major scholars such as Karl Marx, Michael Oakeshott, Althusser, Herbert Marcuse, Habermas, Antonio Gramsci, Lukac, Francis Fukuyama and Samuel Huntington’s views of ideologies are highlighted here. Marx used the term ideology in two interrelated senses, first idealism and second an apologetic body of thought. For Marx, a society is characterized by two types of ideology, namely the dominant and the subordinate. Michael Oakeshott says that an ideology is an abridgement of a tradition. His statements about ideology occur in Political Education. In Althusser’s view ideology represents an imaginary distortion of the real relations of individuals to the relations of production, and to the relations that derive from them. Marcuse analyses the three constitutive components of the totalitarian ideology - universalism, naturalism and political existentialism. According to Habermas, ideologies are a set of beliefs that dissolve when they are called into question since they are maintained only by restricting systematically free and public discourse. Lukac’s study of ideology, history and class consciousness is equally concerned with the problem of mediation and relativism. Francis Fukuyama is also quite right in asserting that the notion of human progress is not outdated. Samuel Huntington has argued that the world is moving into a period of clash civilization, in which the primary identification of people will not be ideological, as during the Cold War, but cultural. People separated by ideology but united by culture come together. Ideologies from the First to the Third World are also included here.